Gareth Cox, Seóirse Bodley (2010) - Elliott, Robin (Journal of the Society for Musicology in Ireland, 2011)
A review of Gareth Cox, Seóirse Bodley, Field Day Music, 4 (Dublin: Field Day Publications, 2010), ISBN 978-0-946755-48-6.